A systematic literature review of injury epidemiology and surveillance practices in elite adult female field-based team sport - Gilhooly, M.; Cahalan, R.; O'Sullivan, K.; Norton, K. (Journal of Science and Medicine in Sport, 2023)
Objectives: To describe injury incidence and surveillance practices in elite adult female field-based team sports.